COMPACTAÇÃO DO SOLO PROVOCADA POR MÁQUINAS AGRÍCOLAS UTILIZADAS NA COLHEITA DA CANA-DE-AÇÚCAR. - FLORA, Murillo Pereira; GUIMARÃES JÚNNYOR, Wellingthon da Silva; DE MARIA, Isabella Clerici; SILVA, Fagner Luiz Rodrigues; PAES, Leilane Lilia (ANAIS DO ENIC, 2022)
-